JEJAK HISTORIS MADRASAH SERTA TANTANGANNYA DI INDONESIA - Achmad Faisol Haq (Kuttab : Jurnal Ilmu Pendidikan Islam, 2017)
The birth of madrassa (Islamic schools) is a response to Islamic education in dealing with the Dutch education policy, initially arriving in Indonesia to trade following the Indonesia’s abundant natural resources. Even, it was determined to take control of the Indonesia’s territory by propagating its teachings, popularly known as 3G namely, Glory, Gold, and Gospel. On account of this phenomenon, the madrassa appeared as Islamic educational institutions used as a means of transfering knowledge in addition to considerably having strateges, especially in shaping the soul of patriotism of the nation children.Keywords: Madrassa, Islamic education, patriotism